2018
DOI: 10.1039/c8ra00531a
|View full text |Cite
|
Sign up to set email alerts
|

A correlation study of biological activity and molecular docking of Asp and Glu linked bis-hydrazones of quinazolinones

Abstract: The present investigation involves the synthesis and spectroscopic and biological activity studies of the bis-hydrazones of quinazolinones derived from aspartic acid and glutamic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our previous efforts have identified that the introduction of aromatic heterocycles, such as imidazole, [ 30 ] quinazolinones, [ 31 ] piperazine, [ 28 ] and benzene‐fused azoles like benzoisoxazole [ 26 ] and benzisothiazole [ 32 ] into target molecules could highly improve the antimicrobial, antioxidant, and anti‐inflammatory activities. In this study, we were particularly interested in using heterocycles 1 , 2 , and 3 , as the basis of the design was to concentrate on amidation at the C‐terminus and creating bis ‐urea or thiourea at the N‐terminus and the ε‐amino groups of lysine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous efforts have identified that the introduction of aromatic heterocycles, such as imidazole, [ 30 ] quinazolinones, [ 31 ] piperazine, [ 28 ] and benzene‐fused azoles like benzoisoxazole [ 26 ] and benzisothiazole [ 32 ] into target molecules could highly improve the antimicrobial, antioxidant, and anti‐inflammatory activities. In this study, we were particularly interested in using heterocycles 1 , 2 , and 3 , as the basis of the design was to concentrate on amidation at the C‐terminus and creating bis ‐urea or thiourea at the N‐terminus and the ε‐amino groups of lysine.…”
Section: Resultsmentioning
confidence: 99%
“…As observed in previous work, here also the title compounds exerted better results compared to conjugates and just heterocycles ( 1–3 ). [ 31 ] The nature of the substituents present on the phenyl ring affected the biological activity of the compounds to a greater extent. The compounds showed significant effects on the growth of the tested bacterial and fungal strains.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that TNF-α serum level, a pro-inflammatory mediator that contributed to neurotoxicity, depends on the rate of its synthesis as well as on its shedding from the cell surface (a mechanism mainly regulated by TACE). Molecular docking is frequently used to rationalize the inhibitory potential of compounds against selected target proteins and to characterize their behaviour in the binding site to predict affinity and activity [52,53]. Altogether, to corroborate the reported in vivo activity, in silico inhibitory activity experiment of variously identified phytoconstituents against TACE was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Since, the molecular docking of the drug molecule with the receptor gives important information about drug-receptor interactions and is commonly used to nd out the binding orientation of drug candidates to their protein targets in order to predict the affinity and activity. 32 So, depending on the binding affinity score that suggested the predominance of the galloyl substructure of myricetin 3-O-glycoside derivatives (1, 2) over other tested compounds (3)(4)(5)(6)(7)(8).…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%